The impact of illegal land invasions on the spatial and demographic structure of the city : an evaluation of Siyanyanzela, Grabouw - Sixabayi, Awonke (Stellenbosch : Stellenbosch University, 2025)
Thesis (MPhil)--Stellenbosch University, 2025.